Trichoderma asperellum (Samuels, Lieckf & Nirenberg) as a promoter of vegetative growth in soybeans - Chagas Junior, Aloisio Freitas; Chagas, Lillian França Borges; Colonia, Brigitte Sthepani Orozco; Martins, Albert Lennon Lima (Revista de Ciencias Agrícolas, 2022)
With the intensification of the problems encountered in agriculture, the use of microorganisms shows promise. Fungi of the Trichoderma genus are found naturally in the soil and have been; they are used as an active ingredient in biofungicides and have activity as promoters of plant growth. This work aimed to evaluate the efficiency of the commercial product TrichoPlus, containing Trichoderma asperellum (Samuels, Lieckf & Nirenberg) as a promoter of soybean plant growth. Four independent experiments were carried out in different periods between 2019 and 2020. The experiments were conducted in a greenhouse, and biomass and nutrient contents were examined. In the first experiment, among the different rates of TrichoPlus tested (3, 4, 5, and 6 g per kg of seeds), the best dose for most of the characteristics evaluated was 5 g per kg of seed. Hence, the inoculation of TrichoPlus at 5 g per kg of seed in the other experiments showed positive results in the accumulation of biomass, nitrogen, and phosphorus content. Based on the study’s results, the product TrichoPlus, composed of T. asperellum, can be used as an efficient inoculant for promoting soybean plant growth.